Population structure of Gyrinops versteegii within floristic community in Nggalak Protection Forest, Flores Island, Indonesia - Abban Putri Fiqa; SUGENG BUDIHARTA; FEBRINA ARTAULI SIAHAAN; RIDESTI RINDYASTUTI (Society for Indonesian Biodiversity, 2020)
Abstract. Fiqa AP, Budiharta S, Siahaan FA, Rindyastuti R. 2020. Population structure of Gyrinops versteegii within floristic community in Nggalak Protection Forest, Flores Island, Indonesia. Biodiversitas 21: 1561-1568.  Gyrinops versteegii (Gilg) Domke is one of the agarwood-producing plants native to eastern Indonesia with high level of exploitation in its natural habitat. Despite being protected by listing it in the CITES Appendix II, anecdotal evidence suggests that G. versteegii population continues to decline. Yet, there is limited empirical data to support such premise. This study was conducted to evaluate the abundance, population structure and floristic importance position of G.versteegii within vegetation community in its natural habitat in Nggalak Forest, Flores. Vegetation analysis was carried out at four growth stages: mature, immature, saplings, and seedlings stage. The results showed that G. versteegii was abundant in its natural habitat in Nggalak Forest in juvenile stages (i.e. seedlings to immature), but not in mature stage. Population densities for seedlings, saplings and immature stage were 313, 150 and 22 individuals per hectare respectively. G. versteegii also hold important position in the community structure, ranks 28th, 6th, and 14th for seedlings, saplings and immature stages respectively in term of importance value index. The high abundance and floristic importance of G. versteegii at the juvenile stages, but not at mature stages, indicates that rampant and over-exploitation of mature plants is likely the major threat to its population. We recommend to replicate similar study in other G. versteegii distribution areas. If similar pattern is found, conservation intervention in the form of protection of its natural population to sustain the juveniles to grow until mature stage may be required along with encouraging cultivation and reintroduction to enhance the population.